Variability of lung clearance index in clinically stable cystic fibrosis lung disease in school age children - Svedberg, Marcus; Gustafsson, Per M.; Robinson, Paul D.; Rosberg, Monica; Lindblad, Anders (Journal of cystic fibrosis, 2018)
Data on long term variability of Lung Clearance Index (LCI) in Cystic Fibrosis (CF) is urgently needed to guide test result interpretation. Our aim was to evaluate LCI variability in clinically stable CF lung disease in school age children. Paediatric patients, aged 6 to 17years, attending the outpatient CF clinic performed Multiple Breath Nitrogen Washout (Exhalyzer® D) and spirometry every third month over a period of one year. Clinical stability was assessed by the Cystic Fibrosis Clinical Score (CFCS) at each visit. Twentyfive children were recruited: baseline median (range) FEV1% pred. 91 (55–122)%, LCI 9.1 (6.4–18.6), CFCS 15 (12−23). A total of 107 visits were included in the study, of which 93% were defined as clinically stable. In clinically stable visits, within-subject variability of LCI and FEV1% pred. were 10% and 16%, respectively. The upper limit of normal (ULN, 95% percentile) of LCI variability during clinical stability was 17%. LCI within-subject variability was low and comparable to FEV1% pred. which strengthen the use of LCI to monitor lung disease progression in CF patients. An increase in LCI >17% compared to previous LCI-measurement in clinically stable CF patients may therefore indicate early lung disease progression.